The Perbandingan Toksisitas Supernatan dan Endapan Ekstrak Terpurifikasi Daun Mindi (Melia Azedarach L.) terhadap Mortalitas Larva Nyamuk Aedes Aegypti L. - Rachmita Mustika Putri; Dwi Wahyuni; Kamalia Fikri (saintifika, 2022)
One of the efforts to replace chemical insecticides to eradicate DBD is to obtain natural larvicides and it’s so environmentally friendly. Vegetable insecticides are carried out using a purified extraction process. The purpose of this study was to compare the toxicity of the supernatant and precipitated purified extract of mindi leaf (Melia Azedarach L.) on the mortality of Aedes aegypti L mosquito larvae. The samples used in this study ranged from 600-700 Aedes aegypti L mosquito larvae. This study used a design design. Completely Randomized (CRD) and the Minitab 14 for Windows application help to perform the analysis. The results showed the comparison of the toxicity of the purified extract supernatant of mindi leaf (Melia azedarach L). lower with an LC50 value > 1000 while the toxicity of the precipitated purified extract of mindi leaves (Melia azedarach L). higher with LC50 value < 1000. This research can be further tested regarding the magnitude of the toxicity in this study related to the measurement of environmental factors and also related to the KLT test to determine the possibility of new compounds, which are synergistic in the precipitate (fraksi etanol) and supernatant (fraksi n-heksan) in purified mindi leaf extract (Melia azedarach L).